Dette mærkelige kløftede landskab: Bemærkninger til den aktuelle forskning i urbane sociale bevægelser - Birke, Peter (Arbejderhistorie, 2012)
Peter Birke: This Peculiar, Divided Landscape – Commentaries to the Current Research in Urban Social Movemnets, Arbejderhistorie 3/2012, pp. 33-53. This article investigates the reception of urban revolts and urban social movements since the 1960s. It discusses the relationship between the longer history of uprisings, their contemporary media coverage and their historiography. It analyses the origins of conflicting interpretations of the meaning and logic of revolts and / or movements established by historians and social scientists in the aftermath of 1968. By proposing that the notion of “non-normative conflict” (Cloward / Piven) could be useful in an analysis of current urban protests, the article examines the ambivalence of slogans used by the “Right to the City”-movement. In particular, it examines the centrality and the limitations of the concept of “gentrification” as used both within the critical scientific community and the mainstream of urban social movements.